A retrospective study of invasive fungal rhinosinusitis in adults for surgical outcomes at tertiary care hospital - Trivedi, Keval R.; Shah , Chaitry (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: An invasive fungal rhinosinusitis is most lethal form of sinusitis. It includes acute and chronic invasive fungal rhinosinusitis. The most lethal fungi are Aspergillous species and mucormycosis, others are Alternaria, P. boydii and Sprothrix. Endoscopic debridement combined with intravenous antifungals are efficacious in management of invasive fungal rhinosinusitis. Methods: Study conducted at department of otorhinolaryngology, GMERS Medical College and Hospital, Sola, Ahmedabad. The period of the study October 2020 to October 2022. Total 100 cases taken. All cases of biopsy proven invasive fungal rhinosinusitis above the age of 18 years are included in this study. Oral and written consent taken from all included patients. A nasal endoscopy followed by KOH mount, magnetic resonance imaging – peripheral nervous system (MRI PNS) done. Results: In our study, 57% patients were surgically treated with functional endoscopic sinus surgery, 23% patients treated with modified Denker’s approach debridement. On basis of MRI PNS, nasal endoscopy and symptomatic improvement of the disease, only 10 patients have recurrence of disease and 90 patients are completely recovered after surgical and medical management. Conclusions: Maintaining high index of suspicion in at risk patient populations, followed by prompt evaluation and management is crucial in suspected invasive fungal rhinosinusitis. Early management with antifungal e.g. Amphotericin B intravenous injections, tab Posaconazole, tab Voriconazole and surgical intervention e.g. FESS, modified Denker’s approach debridement, FESS with middle meatal antrostomy very efficacious in terms of preventing the recurrence and mortality in patients.